Answer:
See below.
Step-by-step explanation:
Try each ordered pair in the equation. Each ordered pair is of the form (x, y). Replace x and y in the equation by values of x and y, respectively, in each ordered pair. Whichever ordered pair makes the equation a true statement is the answer.
For example:
Try (2, 3):
2x + 3y = 10
2(2) + 3(3) = 10
4 + 9 = 10
13 = 10
Since 13 = 10 is a false statement, (2, 3) is not a solution.
Try (2, 2):
2x + 3y = 10
2(2) + 3(2) = 10
4 + 6 = 10
10 = 10
Since 10 = 10 is a true statement, (2, 2) is a solution.